The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1118/1.4801907
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of novel imaging geometries for x‐ray fluorescence computed tomography

Abstract: The authors have demonstrated the feasibility of these two novel approaches to XFCT imaging. While they use synchrotron radiation in this demonstration, the geometries could readily be translated to laboratory systems based on tube sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…The characteristic X-rays are collected by a non-imaging X-ray detector, and, in the absence of significant attenuation, the height or area of the measured characteristic X-ray peak can be directly related to the line integral through the elemental distribution map. The object is then scanned and rotated through the illumination beam in order to acquire a complete sinogram of line integrals in a first-generation tomographic acquisition [8]–[14]. A standard analytic or iterative CT algorithm can then be used for image reconstruction, although in the presence of attenuation, alternative models and methods are needed [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic X-rays are collected by a non-imaging X-ray detector, and, in the absence of significant attenuation, the height or area of the measured characteristic X-ray peak can be directly related to the line integral through the elemental distribution map. The object is then scanned and rotated through the illumination beam in order to acquire a complete sinogram of line integrals in a first-generation tomographic acquisition [8]–[14]. A standard analytic or iterative CT algorithm can then be used for image reconstruction, although in the presence of attenuation, alternative models and methods are needed [15].…”
Section: Introductionmentioning
confidence: 99%
“…We have also carried out a preliminary experimental study to demonstrate the feasibility of XFET with a synchrotron X-ray source [14]. The present paper demonstrates the translation of our approach to the benchtop and discusses methods used for performing spectroscopically accurate single-photon counting in a detector not natively designed for such work.…”
Section: Introductionmentioning
confidence: 99%
“…Note that in a very recent study, Fu et al . used synchrotron radiation and novel imaging geometries to image osmium in zebra fish with L-shell XFCT (Fu et al , 2013). …”
Section: Introductionmentioning
confidence: 99%
“…However, the image acquisition time was long because it was necessary to rotate the phantoms and translate the detectors to obtain full three-dimensional (3D) images. The research by Meng et al 45 , Fu et al 46 , and Groll et al 47 demonstrated improved images obtained by the pinhole-based system and 2D position-sensitive detectors computationally and experimentally. In these studies, pinhole collimation with a 2D X-ray charge-coupled device (CCD) camera (Model #934N, Andor Technology), which has a detection efficiency of ~30% at 10 keV and ~15% at 15 keV, was used to detect iron, zinc, and bromine solutions, whose energies of K-shell fluorescence X-rays range from 6.4 keV to 13.3 keV.…”
mentioning
confidence: 99%